2020
DOI: 10.3390/su12062410
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of High-speed Rail on Sustainable Economic Development: Evidence from the Central Part of China

Abstract: To give full play to the role of high-speed rail (HSR) in promoting sustainable economic development, the models that can calculate and describe the impacts of HSR on the sustainable economy are required. However, little attention has been paid so far to building such models. To address this, the paper puts forward the definition of sustainable economic development, especially that of China. Based on the definition, the paper proposes the indicators of sustainable economic development for China from industry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…The findings of this study are supported by a study that also found that the opening of the HSR tends to impact economic growth significantly, and, in this way, the study findings are strongly supported [22]. Researchers have further enhanced studies on the impact of HSR on economic development [63]. This study evaluated the HSR impact on sustainable economic development and found that they are significantly related to each other.…”
Section: Hsr Along With Quality Of Place Improves Regional Economic Growthsupporting
confidence: 73%
“…The findings of this study are supported by a study that also found that the opening of the HSR tends to impact economic growth significantly, and, in this way, the study findings are strongly supported [22]. Researchers have further enhanced studies on the impact of HSR on economic development [63]. This study evaluated the HSR impact on sustainable economic development and found that they are significantly related to each other.…”
Section: Hsr Along With Quality Of Place Improves Regional Economic Growthsupporting
confidence: 73%
“…Scientific and technical advancements have spurred economic growth [52]. HSR is an important part of contemporary transportation technology innovation to enhance mobility and accessibility [53][54][55][56][57].…”
Section: Innovationsmentioning
confidence: 99%
“…Небольшие же предприятия с целью сокращения транспортных расходов склоны к расположению вблизи мест реализации товаров. Следовательно, при грамотном планировании развитие высокоскоростного железнодорожного сообщения способствует усилению агломерационных процессов, углублению специализации и повышению эффективности производства [16]. Ожидается, что от улучшения транспортной доступности выигрывают все населенные пункты, подключенные к системе высокоскоростного железнодорожного сообщения, однако, экономические исследования свидетельствуют о неоднородности выгод вследствие развития транспортной сети.…”
Section: транспортная доступность как индикатор экономического развития территорийunclassified